Isolated Adrenocorticotropic Hormone Deficiency Following Chronic Subdural Hematoma in an Elderly Man: Is There a Connection? - Suzuki, Satoshi; Suzuki, Keiko (Internal Medicine, 2017)
The delayed diagnosis of adrenal insufficiency is relatively common because its symptoms are non-specific. One of the causes of adrenal insufficiency is isolated adrenocorticotropic hormone deficiency (IAD), which is sometimes caused by traumatic brain injury. Indeed, severe head trauma is considered to contribute to the incidence of this disease. However, the relationship between milder head trauma—such as chronic subdural hematoma — and the occurrence of hormonal deficiency is uncertain. We herein report the case of a 79-year-old man with IAD who presented with leg edema and pain in his extremities following a recent history of chronic subdural hematoma.